Preparation of Carboxymethyl Cellulose-g- Poly(acrylamide)/Attapulgite Porous Monolith With an Eco-Friendly Pickering-MIPE Template for Ce(III) and Gd(III) Adsorption - Wang, Feng; Zhu, Yongfeng; Wang, Aiqin (Frontiers in Chemistry, 2020)
Due to the high specific surface and metal-binding functional groups in the crosslinked polymeric networks, the monolith materials incorporation with porous structure have been considered as one kind of the most efficient adsorbents for rare earth elements recovery. Herein, a facile and novel monolithic multi-porous carboxymethyl cellulose-g-poly(acrylamide)/attapulgite was synthesized by the free radical polymerization via green vegetable oil-in-water Pickering medium internal phase emulsion (O/W Pickering-MIPEs), which was synergically stabilized by attapulgite and tween-20. The homogenizer rotating speed and time were performed to form stable Pickering-MIPEs. The effect of types of oil phase on the formation of Pickering-MIPEs were investigated with stability test and rheological characterization. The structure and composition of the prepared porous material with eight kind of vegetable oil were characterized by FTIR and SEM. The results indicate that the obtained materials with abundant interconnected porous are comparable to that fabrication with Pickering-HIPEs templates. The adsorption experiment demonstrate that, the prepared material have a fast capture rate and high adsorption capacities for Ce(III) and Gd(III), respectively. The saturation adsorption capacities for Ce(III) and Gd(III) are 205.48 and 216.73 mg/g respectively, which can be reached within 30min. Moreover, the monolith materials exhibit excellent regeneration ability and reusability. This work provides a feasible and eco-friendly pathway for the construction of the multi-porous adsorbent for adsorption and separation application.